Cuidados de enfermería en pacientes con cáncer de mama en atención primaria. Ecuador, 2018. - Moyano Cesen, Carolina Estefanía (2019)
Cancer has become one of the leading causes of death worldwide, with breast cancer being the most frequent. This malignant tumor is one of the biggest public health problems in Latin America due to its incidence, prevalence, morbidity and mortality, considering it a chronic disease that impacts the quality of life of the people who suffer from it. For this reason it is necessary to perform a literature review to analyze nursing care in patients with breast cancer in primary care focused on promotion, prevention, and rehabilitation, the type of study was bibliographical criteria were applied to select the information with relevance , completeness and topicality, citing articles published in English Spanish and Portuguese using search engines such as: Google Scholar, Dialnet Repositories of thesis, Redalyc, on official websites such as the World Health Organization, Pan American Health Organization, Ministry of Public Health, We found 320 documents with information on the subject. The study population was made up of all 62 articles published in journals indexed in regional and global bases, during the period between 2012 and 2019. For the search, inclusion criteria were used, such as: "Nursing care", " breast cancer "," first level of health care "and as exclusion criteria were taken into account the terms" diagnostic methods, breast cancer risks, socioeconomic factors, for the writing of documentary bibliographic research, Vancouver standards were used. The results highlight the role that the nurse should play at the primary care levels, however there are no protocols or clinical practice guidelines that guide the nursing action for patients with breast cancer in Ecuador. But clinical practice guides from Mexico were found with information relevant to the subject.